KEBERHASILAN PENGEMBANGAN DESA WISATA BATU LINTANG KABUPATEN KAPUAS HULU KALIMANTAN BARAT - Sim, Emiliani Nindy Diana Rusega (Universitas Kapuas Sintang, 2025)
The development of tourism villages in Indonesia is one of the important strategies in improving the regional economy and preserving local culture. Batu Lintang Village in Kapuas Hulu Regency, West Kalimantan, is one example of a village that has successfully developed into a leading tourist destination. This success was marked by winning first place in the Tourism Village Attractiveness category at the 2024 Anugerah Desa Wisata Indonesia (ADWI) event, after competing with more than 6,000 other tourism villages throughout Indonesia. As a tourist village, Batu Lintang Village offers a unique attraction, namely a combination of natural and cultural tourism. The Dayak Iban people who inhabit this village are known for their commitment to protecting the environment and maintaining ancestral traditions, such as the pristine betang houses in Sungai Utik Hamlet. In addition, the natural beauty around the village, including the customary forest and the presence of hornbills, makes this village potential for ecotourism development. The success of tourism village development is inseparable from various supporting factors, such as local community involvement, government support, and the right strategy in managing natural and cultural resources. Therefore, this research was conducted to understand more deeply how Batu Lintang Village achieved its success as a tourist village.